Md Nazrul Islam y Md Saidul Islam. 2020. Islam and Democracy in South Asia. The Case of Bangladesh. Cham: Springer. 331 pp. ISBN 9783030429089. Ebook ISBN 9783030429096. https://doi.org/10.1007/978-3-030-42909-6 - Taussig, Sylvie (Estudios de Asia y África, 2022)
Md Nazrul Islam y Md Saidul Islam. 2020. Islam and Democracy in South Asia. The Case of Bangladesh. Cham: Springer. 331 pp. ISBN 9783030429089. Ebook ISBN 9783030429096. https://doi.org/10.1007/978-3-030-42909-6